Assessment of the Time Utilization of the Community Health Officers (CHO) of Bhavnagar District, Gujarat: A Cross-sectional Study - Kartik B Prajapati; Kailesh D Bhalani (Healthline)
Introduction: To attain "universal health coverage" and "health of all", a new cadre namely Community Health Officer (CHO) was introduced at HWC (Health and Wellness Center). In the community, CHO serves as the initial point of contact and source of information for health-related issues. Objective: To assess the utilization of time of CHO at HWCs, Bhavnagar. Method: Out of 63 CHOs with experience of more than 1 year in Bhavnagar district, 30 CHOs were selected randomly for utilization of time. Each CHO was accompanied during their duty hours for all working days of a week. Time spent by a CHO in different activities was recorded. Data were analyzed by using Epi Info Software. Results: It was observed that on an average, CHOs remained on duty for 93% of their duty hours. Around 29.61% of their actual on-duty-time (per week) was used for the personal work, while 17.34% of their on-duty-time was used in OPD, 14.36 % in COVID-19 related work and 14.13% in administration work. Conclusion: The analysis revealed that CHOs spent 93% of their scheduled duty hours on the job. CHOs spent almost one third of their duty hours for the personal work.